INDONESIAN EFL TEACHERS’ PERCEPTION ON THE IMPLEMENTATION OF 2013 ENGLISH CURRICULUM - Endang Darsih (University of Kuningan, 2014)
Abstract: Since 2014-2015 academic year, the Ministry of Education and Culture of Republic of Indonesia finally decided to implement the 2013 Curriculum. Restoring character education and improving students’ creative thinking are the main reasons of the new curriculum development. This study employed teachers’ understanding and perception on the implementation of 2013 English Curriculum and identified problems encountered by the teachers in implementing the 2013 English curriculum. Through qualitative design, the study was conducted at one of vocational high schools in Kuningan, West Java. This study reveals that the teacher’s understanding toward 2013 curriculum is quite close to the basic principles of the curriculum and most of teachers claim that the new curriculum cannot be easily implemented at the moment since they find several problems in implementing 2013 English curriculum. They got difficulties in applying new learning revolution, developing assessment rubrics and the shortage of English duration at school will not ensure to improve students’ competence. It also recommended that the teachers should put more efforts on applying the 2013 curriculum in the teaching and learning process by joining any training, workshop and improve their creativity and adapt to the advance of knowledge and technology.Keywords: 2013 English Curriculum, teachers’ understanding, teachers’ perception